Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.joc.6b00252
|View full text |Cite
|
Sign up to set email alerts
|

Calix[3]carbazole: One-Step Synthesis and Host–Guest Binding

Abstract: The one-step synthetic strategy for the preparation of the hitherto unknown calix[3]carbazole from readily available starting materials is described. Calix[3]carbazole is obtained in 20% yield, and it could selectively bind the N(C2H5)4(+) cation (tetraethylammonium, TEA) via cation-π interactions. The experimental and modeling results indicate that calix[3]carbazole possesses a larger π-cavity as well as a better chromophoric property than the traditional phenol-based macrocycles, and thus is capable of bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…37,41 The resulting binding constants were K ¼ 50 AE 3, 91 AE 4, and 128 AE 9 M À1 for the complex formation between [3]CPT-Hex and 4, 5, and 6, respectively. For the ammonium cations 5 and 6, the binding constants are larger than that reported for calix [3]carbazole 13 with the tetraethylammonium cation (up to 66.8 M À1 ).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…37,41 The resulting binding constants were K ¼ 50 AE 3, 91 AE 4, and 128 AE 9 M À1 for the complex formation between [3]CPT-Hex and 4, 5, and 6, respectively. For the ammonium cations 5 and 6, the binding constants are larger than that reported for calix [3]carbazole 13 with the tetraethylammonium cation (up to 66.8 M À1 ).…”
Section: Resultsmentioning
confidence: 56%
“…35 For N-arylphenothiazines, emissions around or above 500 nm and such large Stokes shifts were only observed with electron-withdrawing substituents at the aryl group (CN or CF 3 ), 35 Finally, we performed host-guest studies of [3]CPT-Hex with different guests. For comparison with the recently reported calix [3]carbazole, 13 we chose the imidazole derivative 4 as a neutral guest, which shows high binding constants (up to 10 4 M À1 ) towards pillar [5]arenes, 36 as well as tetraalkylammonium cations, namely 5 and 6 (Figure 6a). NMR titration experiments 37 of [3]CPT-Hex solutions with these guest molecules showed a shift in the phenothiazine 1 H NMR resonances with increasing guest concentrations (see Figure 6b, spectra for other titrations can be found in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure showed that in the absence of DNA, 2 exhibited only two peaks in the region of 6.9–7.7 ppm, which were assigned to H 1(8) and H 4(5) , respectively. The symmetric and relatively simple 1 H NMR profile indicated that the unbound/free 2 adopted either i) a flatten partial cone (or saddle) conformation, or ii) a rapidly inverted cone conformation on the NMR time scale . Due to the electronic repulsion of the oxygen atoms of 2,7‐dimethoxyl groups of neighbors’ carbazolyl moieties of 2 , the former case would be more possible.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported a novel series of non-phenol-based macrocycles: calixcarbazoles . The cavity of calix[3]­carbazole, the smallest one among those carbazolyl macrocycles, is already larger than that of calix[4]­arene.…”
mentioning
confidence: 99%